Tindakan Hakim Dalam Menilai Kekuatan Alat Bukti Keterangan Saksi yang Berbeda Antara Di Depan Penyidik Dengan Di Persidangan - Marwanti, Leni; , Hartono, S.H., M.Hum; , Muchamad Iksan, S.H., M.H (2015)
The purpose of this study was to determine: (1) the actions of judges in making decisions if there is a difference different witness testimony in front of the investigator with at the hearing; (2) Criteria for evidence statements of witnesses are considered legitimate by the judge. This research includes juridical empirical. Research conducted at the District Court of Surakarta. Data sources using primary data from interviews, observation, and literature study. Data were analyzed using qualitative analysis. The results showed that: (1) The judge in assessing the strength of evidence statements of witnesses are different between in front of the investigator with before the trial, judges then to obtain the attendance of witnesses verbalisan. The judge may remind the witness that if the information submitted is not correct then the witness can be imprisoned for giving testimony / perjury. Based on the judge's decision number 253 / Pid.B / 2007 / PN.SKa, witness information provided does not affect the decision of the judge handed down because the witness who does not have value given the force of law, because it is not equipped with the evidence and contrary to the description given by other witnesses; (2) Criteria for evidence statements of witnesses are considered legitimate by the judge is witness testimony given under oath, witness testimony given before trial, and the judge only that is worth assessing witness testimony as evidence. Keywords: The testimony that contrast, Judge Actions